DETECTION OF ANTIBIOTICS RESIDUES IN PROTEIN CONTAINING DIETS (MEAT AND EGGS) OF HUMAN THROUGH DIFFERENT METHODS - Neelma Ashraf; Abid Rashid et al. (Journal of University Medical & Dental College, 2018)
Bacterial and drug contaminants are the major causes of meat and egg borne illness in human. The elaborated methods described in this study, fulﬁl the criteria for a routine screening method, and should be a useful tool for the detection of antibacterial substances in animal feeding stuﬀs. Antibiotics are extremely important class of drugs, as they represent a key component in the strategy used in the control of bacterial infections in both humans and animals. It is therefore important that their use in food animals be done with utmost care; antibiotics should be given at recommended doses and with appropriate supervision. Adequate holding period should be observed in all slaughter animals following therapeutic use of antibiotics. Ideally, the use of antibiotics in food animals by non-veterinarians should be discouraged. Regulatory authorities should also ensure proper meat inspection and drug residues surveillance program should be established in the country to ensure food safety.